EVALUATION OF ANTI-ANXIETY ACTIVITY OF ACTAEA SPICATA LINN. (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Actaea spicata Linn. (Ranunculaceae) has been traditionally used for the treatment of various ailments such as rheumatism, inflammation, nerve diseases, lumbago, scrofula and chorea. Despite a long tradition of use, no systematic phytochemical and pharmacological work has been carried out on this potential plant. Thus, A. spicata was subjected to preliminary anti-anxiety screening studies, with a view to ascertain the verity of its traditional use as an anxiolytic. In the present investigation, roots of the plant were extracted using solvents in order of increasing polarity viz., petroleum ether (60-80C), chloroform, methanol and distilled water. All the crude extracts were evaluated for anti-anxiety activity in mice using elevated plus maze apparatus. Among all these extracts, only methanol extract exhibited significant anti-anxiety activity at a dose of 100 mg/kg in mice with respect to control as well as standard (diazepam, 2 mg/kg). Phytochemical screening showed presence of alkaloids and polyphenols in methanol extract of A. spicata. Thus, Specific methods were adopted to extract total alkaloidal and polyphenol fractions from the plant material and methanol extract of plant, respectively. Polyphenol fraction exhibited significant anxiolytic activity at the dose of 50 mg/kg, while alkaloidal fraction was found to be devoid of any activity.